2020
DOI: 10.1080/14479338.2020.1759427
|View full text |Cite
|
Sign up to set email alerts
|

Organising an early phase of academic engagement: a case study of interactions between engineering and equestrian sports

Abstract: This paper explores the underlying processes of initiating academic engagement, seen from the university perspective. We do so through a longitudinal case study, of the university, Chalmers, and specifically around the engineering subjects, and the development of such relationships with a sector with few such traditions, namely equestrian sports. In terms of how the chosen university has worked to initiate academic engagement, we find, in contrast to existing literature, how, what we call researcher-teachers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…It is, therefore, natural to seek to integrate collaboration-enhancing efforts also with educational initiatives. Hermanson et al (2021) challenge the prevailing focus of the university-industry literature on the activities of university faculty, and suggest that while different in terms of e.g., content and continuity, student-centred collaboration activities deserves further attention by universities and by scholarship seeking to understand their roles in the knowledge economy.…”
Section: Researching the Challenges For Universities In The Knowledge Economy: The Way Aheadmentioning
confidence: 89%
See 1 more Smart Citation
“…It is, therefore, natural to seek to integrate collaboration-enhancing efforts also with educational initiatives. Hermanson et al (2021) challenge the prevailing focus of the university-industry literature on the activities of university faculty, and suggest that while different in terms of e.g., content and continuity, student-centred collaboration activities deserves further attention by universities and by scholarship seeking to understand their roles in the knowledge economy.…”
Section: Researching the Challenges For Universities In The Knowledge Economy: The Way Aheadmentioning
confidence: 89%
“…In their contribution, Hermanson et al (2021) analyse how researchers and the university as an organisation acted to initiate academic engagement and commercialisation, in an area with previously low levels of collaboration, namely engineering and equestrian sports. Previous literature tends to study existing academic engagement, and also has demonstrated the importance of individual researchers with specific characteristics (Perkmann et al, 2021(Perkmann et al, , 2013, but this case study demonstrates a more complex process, at least for new areas.…”
Section: The Articles In This Special Issuementioning
confidence: 99%
“…As a first extensive and realistic framework of university-industry collaboration, we consider the contribution of Bonaccorsi and Piccaluga (1994) that summarized six main categories of organizational forms of UIC, namely: personal informal relationships, personal formal relationships, relationships through the third party, formal targeted and formal un-targeted agreements and common focused structures. The majority of newer contribution builds on this framework, and thus, on the assumption that the majority of university-industry collaborations tend to be driven by individuals and pursued on a discretionary basis (Hermanson et al 2020). Nowadays, it is formally measured in the majority of European countries, how frequently entrepreneurs collaborate with universities, e.g., in terms of the provision of research services, counselling, getting access to unique know-how of researchers, academic technologies or research infrastructure, getting the support with product/service/process development (Rybnicek and Königsgruber 2019).…”
Section: Conceptual Backgroundmentioning
confidence: 99%